Healing of surgical wounds treated with 810nm, 940nm, and 980nm diode lasers in different operation modes - Aytugar, Emre; Unver, Tugba; Bicer Aytugar, Tugce; Celikten, Mert; Selvi, Firat; Canan Alatli, Fatma; Usumez, Aslihan (Annals of Medical Research, 2021)
Aim: The aim of the present study was to analyze the comparative effectiveness of the diode lasers having 3 different wave-lengths (810nm, 940nm, 980nm) and also the different application modes on the cellular basis in animal models.Many surgical instruments like scalpel, electrosurgery, and different laser types can be used for surgical incisions. Each of these have their own advantages and disadvantages.Material and Methods: 10 mm in length and 1 mm in depth dorsal skin incisions were created on 18 male Wistar albino rats via 3 different laser wave-lengths: 810nm (Gigaa, Cheese, China), 940nm(Epic 10, Biolase, USA) and 980nm (SIROlaser Advance, Sirona, Bensheim, Germany). The animals were sacrificed at either post-operative 24 hours, 3 days or 1 week. All incision sites were removed by excisional biopsies and the samples underwent histopathological evaluation.Results: There were no statistically significant differences in thermal changes, inflammation, and fibrosis in all wave-length groups (p>0.05). The chopped mode of irradiation of all wave-lengths showed significant increase in epithelial closure following the operation (p0.05). There were significant increases of the granulation tissue formation on the 3rd post-operative day with 940nm using chopped mode and 810nm in continuous mode (p0.05).Conclusion: Pulsed mode of lasers accelerates the epithelization regardless of the wave-lengths while 940nm and 810nm lasers in continuous mode speeds up the granulation tissue formation.Keywords: Diode lasers; wound healing; surgery.
Keywords: Diode lasers; wound healing; surgery.